ECONOMIC STRATEGY IN THE AGE OF ARTIFICIAL INTELLIGENCE: HARNESSING AI FOR SUSTAINABLE GROWTH - Lucky Mahesa Yahya; Loso Judijanto; Moh. Gufron Romadhoni (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2024)
The purpose of this study is to analyse the contribution of artificial intelligence (AI) to the achievement of sustainable economic growth. The method used was a literature study, where data and information were collected from various sources including scientific journal articles, research reports, and relevant publications. The analysis involved synthesising findings from existing literature to identify the key role of AI in supporting sustainability in social, economic, and environmental aspects. The results indicated that AI plays a significant role in maximising resource use efficiency, reducing wastage, and promoting the use of renewable energy. AI also contributes to increased innovation in industry and more sustainable management of natural resources. In the environmental context, AI has proven effective in modelling and predicting climate change and addressing biodiversity challenges. AI also has the potential to increase public engagement and awareness in sustainability practices. The research conclusion suggests that integrating AI in sustainable development strategies can stimulate economic growth while ensuring a healthy environmental balance for a sustainable future.